Perbandingan Partisipasi Perempuan Dalam Pembangunan Gampong - Nuzulul Khaira; Zahrul Fuady; Atika Aditya (Bayt ElHikmah: Journal of Islamic Architecture and Locality, 2026)
Women’s participation in village development is an important element in promoting sustainable development. Yet, village profiles differ widely, so it remains unclear whether the forms this participation takes are shaped more by a village’s economic base than by uniform regulation. This study compares two villages with contrasting economic profiles, Gampong Lampulo, a fishing-based coastal village, and Gampong Deah Raya, which combines small-trade and religious-tourism activity, to examine the forms of women’s participation in these two villages across five sectors of village development: education, economy, health, tourism, and socio-cultural activities.